Sustainability Society sebagai Pendorong Inovasi Menuju Model Corporate Social Entrepreneurship - Richa Nahdalaily Fathara; Margo Purnomo; Ratih Purbasari (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri Palembang, 2021)
Business-level competition in the Indonesian culinary field continues to increase. This condition causes business actors to adapt to the existing environment. One of the effective ways that companies can do to achieve sustainability is to innovate. The importance of innovation today is not only aimed at sustainability, but also for sustainable development goals (SDG's). This demand for sustainable development for the community has also created a new awareness in the corporate world that meeting the sustainability needs of the community not only helps to minimize risk, but can also create opportunities to create shared value. Therefore, this study aims to show how companies respond to external sustainability challenges by following a corporate social entrepreneurship approach that allows companies to create shared value. It aims to enrich the existing corporate entrepreneurship model and present a corporate social entrepreneurship model.